Protecting FDI contributing to host countries' development: The rise of the "forgotten" Salini criterion as part of the definition of investment - Daniela Gómez Altamirano (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2021)
Countries are increasingly focusing on attracting quality FDI. This Perspective explores the potential of requiring "contribution to the development of the host State" for an investment to be protected under an IIA and the alternatives that policymakers have to support sustainable development, as reflected in the Sustainable Development Goals.
Keywords: 330